Service learning in Zagreb University: how far have we gone? - Kišiček, Sanja (Array, 2008)
The goal of this paper is to discuss the recent development and evaluation of service learning (SL) methodology in information science curriculum. In the Academic Year 2006/07 we introduced new educational methodology into our curriculum transforming the old teaching style and giving students more place to apply the theory they learned. Also, SL explores the possibilities of transforming our university into a place that meets the needs of the new economic reality of changing markets and rapidly developing technology. We integrated that methodology with the ICT in order to achieve better learning outcomes and we present both the successful and unsuccessful recently finished service learning projects in this paper. Finally, for the first time this paper brings all the advantages and drawbacks of the application of SL methodology into Bologna process in our University.